2018
DOI: 10.1017/cjn.2018.363
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Personalized Subcutaneous Immunoglobulin Treatment Program for Neurological Patients

Abstract: BackgroundSubcutaneous immunoglobulin (SCIg) treatment has been shown to control symptoms and improve overall satisfaction in patients with neurological disorders. However, a large injection volume can be overwhelming and a barrier to successful SCIg treatment. We established a nurse-led individualized approach program to facilitate a smooth and successful treatment transition from intravenous immunoglobulin (IVIg) to SCIg. The program involved a lead nurse to provide two or more individual educational session… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…37 A support program for patients opting to transition to SCIg is important to build confidence with selfadministration for successful long-term adherence. 64 In one study, a 20 Van Schaik et al reported that the rate of headaches was low for SCIg (7%) and this was maintained during the OLE study (5%). 16,33 In comparison, headaches associated with IVIg have been reported in other studies as ranging between 32% and 62% of patients.…”
Section: Long-term Adherencementioning
confidence: 98%
See 2 more Smart Citations
“…37 A support program for patients opting to transition to SCIg is important to build confidence with selfadministration for successful long-term adherence. 64 In one study, a 20 Van Schaik et al reported that the rate of headaches was low for SCIg (7%) and this was maintained during the OLE study (5%). 16,33 In comparison, headaches associated with IVIg have been reported in other studies as ranging between 32% and 62% of patients.…”
Section: Long-term Adherencementioning
confidence: 98%
“… 37 A support program for patients opting to transition to SCIg is important to build confidence with self‐administration for successful long‐term adherence. 64 In one study, a nurse‐led individualized program that included teaching sessions, written materials, and a clear care plan helped to successfully transition patients with neurological disorders from IVIg to SCIg. In this study, SCIg retention rates were 90% (n = 17/19) at 6 mo and 79% (n = 15/19) at 12 mo.…”
Section: Practicalities Of Using Scig In Cidpmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the Canadian Journal of Neurological Sciences, Suleman et al describe a multi-disciplinary approach to subcutaneous immunoglobulin (SCIG) administration in patients with immune neurological conditions in the article "Evaluation of a Personalized Subcutaneous Immunoglobulin Treatment Program for a Neurological Patients". 1 In their study, a nurse-led program transitioned patients receiving 10% intravenous immunoglobulin (IVIG) to 20% SCIG using a conversion of 1:1.2 (IVIG:SCIG), with a 79% retention rate at 12 months, no serious adverse events and only one minor cutaneous dermatological adverse event reported. In their study, which included patients with chronic inflammatory demyelinating polyneuropathy (CIDP), multifocal motor neuropathy (MMN), myasthenia gravis (MG) or Lambert Eaton Myasthenic Syndrome, four patients (three with MMN) were not able to complete the 12 months of SCIG treatment and required either supplemental IVIG infusions or a transition back to IVIG treatment.…”
mentioning
confidence: 99%
“…In this issue of the Canadian Journal of Neurological Sciences, Suleman et al describe a multi-disciplinary approach to subcutaneous immunoglobulin (SCIG) administration in patients with immune neurological conditions in the article “Evaluation of a Personalized Subcutaneous Immunoglobulin Treatment Program for a Neurological Patients” 1 . In their study, a nurse-led program transitioned patients receiving 10% intravenous immunoglobulin (IVIG) to 20% SCIG using a conversion of 1:1.2 (IVIG:SCIG), with a 79% retention rate at 12 months, no serious adverse events and only one minor cutaneous dermatological adverse event reported.…”
mentioning
confidence: 99%